Viability of Pathologic Cartilage Fragments as a Source for Autologous Chondrocyte Cultures. (April 2016) - Guillén-García, Pedro; Rodríguez-Iñigo, Elena; Guillén-Vicente, Isabel; Guillén-Vicente, Marta; Fernández-Jaén, Tomás; Concejero, Vicente; Val, Daniel; Maestro, Antonio; Abelow, Steve; López-Alcorocho, Juan Manuel
Objective: To study if a culture of chondrocytes can be obtained from pathologic hyaline cartilage (PHC) fragments. Design: Twenty-five men and 9 women with osteochondritis dissecans (OCD) in 11 cases, arthrosis in 13 patients, and trauma in the remaining 10 cases were included. The PHC fragments and a small sample of the next healthy cartilage were extracted by arthroscopy. According to the appearance, the PHC samples were divided into fixed (3 cases), flapped (6 patients), or loose bodies (25 cases), depending on the attachment degree of the cartilage to the subchondral bone. Approximately half of each pathologic sample and the whole healthy one were digested to isolate the cells trying to establish the cell culture. Results: We were able to establish a cell culture in 7 out of 34 (20.6%) PHC samples (positive samples), whereas in the remaining 27 (79.4%) no cell growth was observed (negative samples). Most of the negative samples were loose bodies ( P = 0.005) taken from patients with OCD or arthrosis ( P = 0.001) with an evolution time of more than 1 year ( P < 0.001). The best binary logistic regression model ( P < 0.001) showed that the only factor affecting the establishment of cell culture was the evolution time ( P = 0.044). Conclusion: It is possible to culture chondrocytes from osteochondral fragments if they are traumatic, within a year of injury and not from fragments due to arthrosis or OCD.